Răspuns :
a) (23-x):6=3
23-x=3*6
23-x=18
23-18=x
x=5
b) (23-5*x):9=2
23-5x=9*2
23-5x=18
23-18=5x
5=5x
x=1
c) 24:(5-x)=6
5-x=24:6
5-x=4
5-4=x
x=1
d) 32:(13-5*x)=4
13-5x=32:4
13-5x=8
13-8=5x
5=5x
x=1
e) 13-(14:x)=18-7
13-14:x=11
14:x=13-11
14:x=2
14:2=x
x=7
a) (23-x) :6 = 3
23-x = 3· 6
23 - x = 18
-x = 18 -23
-x = -5
x = -5 : (-1)
x = 5.
b) ( 23-5x) : 9 = 2
23 - 5x = 2·9
23-5x = 18
-5x = 18 - 26
-5x = -5
x = -5 : (-5)
x = 1.
c) 24 : (5-x) = 6
5-x = 24 : 6
5-x = 4
-x = 4-5
-x = -1
x = -1 : (-1)
x = 1.
d) 32 : (13-5x) = 4
13 - 5x = 32 : 4
13 - 5x = 8
-5x = 8 - 13
-5x = -5
x = -5 : (-5)
x = 1.
e)13 - 14 : X = 18 - 7
13 - 14:x = 11
-14:x = 11-13
-14:x = -2
x =-14 : (-2)
x = 7
23-x = 3· 6
23 - x = 18
-x = 18 -23
-x = -5
x = -5 : (-1)
x = 5.
b) ( 23-5x) : 9 = 2
23 - 5x = 2·9
23-5x = 18
-5x = 18 - 26
-5x = -5
x = -5 : (-5)
x = 1.
c) 24 : (5-x) = 6
5-x = 24 : 6
5-x = 4
-x = 4-5
-x = -1
x = -1 : (-1)
x = 1.
d) 32 : (13-5x) = 4
13 - 5x = 32 : 4
13 - 5x = 8
-5x = 8 - 13
-5x = -5
x = -5 : (-5)
x = 1.
e)13 - 14 : X = 18 - 7
13 - 14:x = 11
-14:x = 11-13
-14:x = -2
x =-14 : (-2)
x = 7